2019
DOI: 10.1080/10400435.2018.1522524
|View full text |Cite
|
Sign up to set email alerts
|

Assistive technologies for severe and profound hearing loss: Beyond hearing aids and implants

Abstract: Assistive technologies offer capabilities that were previously inaccessible to individuals with severe and profound hearing loss who have no or limited access to hearing aids and implants. This literature review aims to explore existing assistive technologies and identify what still needs to be done. It is found that there is a lack of focus on the overall objectives of assistive technologies. In addition, several other issues are identified i.e. only a very small number of assistive technologies developed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Similarly, McKee et al highlighted that the deaf community views deafness as a cultural identity, rather than a disability [41]. On this note, Hermawati and Pieri suggested that studying the acceptance and development of assistive technologies should focus on the overall welfare of DHH populations beyond only hearing-related challenges [20], such as social and cultural norms in DHH online communities.…”
Section: Accessibility Of Information and Communication Technologies ...mentioning
confidence: 99%
“…Similarly, McKee et al highlighted that the deaf community views deafness as a cultural identity, rather than a disability [41]. On this note, Hermawati and Pieri suggested that studying the acceptance and development of assistive technologies should focus on the overall welfare of DHH populations beyond only hearing-related challenges [20], such as social and cultural norms in DHH online communities.…”
Section: Accessibility Of Information and Communication Technologies ...mentioning
confidence: 99%
“…Te game encourages users to engage with a virtual environment, allowing them to learn sign language in a novel and enjoyable way. It is regarded as a language of Portuguese Sign Language [23] to use sign language signals to consolidate similar aims and purposes. ISL translation system and Indian Sign Language (ISL) translation device for learning sign language pictures or continuous video images (of the public) are captured using a microphone or USB camera and can be interpreted by an application.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The requirements for these tools must be further studied in order to improve usability and usefulness [38]. Assistive technologies for the hearing-impaired must be designed to fit for all and more commercialised as many are only designed for research purposes [39,27,40]. Many solutions that are present are flawed as most are one-sided, they either work for a certain group of hearing deficient individuals (deaf, hard of hearing, or mute) or they work only under specifically predefined situations.…”
Section: Overview Of Current Toolsmentioning
confidence: 99%